2012
DOI: 10.1002/app.38487
|View full text |Cite
|
Sign up to set email alerts
|

Morphology of polypropylene/silica nano‐ and microcomposites

Abstract: The aim of this study was to compare the effects of different silica grades on the structure and morphology of isotactic polypropylene (iPP)/silica composites to better understand their structure-property relationships. Isotactic polypropylene composites with 2, 4, 6, 8 vol % of added silica fillers differing in particle size (micro-vs. nanosilica) and surface modification (untreated vs. treated surface) were prepared by nonisothermal compression molding and characterized by different methods. The addition of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
39
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 21 publications
(41 citation statements)
references
References 27 publications
2
39
0
Order By: Relevance
“…The addition of all silica grades to plain iPP decreases the size of spherulite due to their nucleation ability. [15] Even the treated nonpolar S-D17 microsilica with minimal nucleation ability decreases the spherulite size, as illustrated by polarized optical micrographs in Figs. 6 a,b. On the other hand, an increase in spherulite size with the increasing elastomer content (Fig.…”
Section: Spherulitic Morphology Of Ipp/sio 2 /Sebs-g-ma Compositesmentioning
confidence: 93%
See 2 more Smart Citations
“…The addition of all silica grades to plain iPP decreases the size of spherulite due to their nucleation ability. [15] Even the treated nonpolar S-D17 microsilica with minimal nucleation ability decreases the spherulite size, as illustrated by polarized optical micrographs in Figs. 6 a,b. On the other hand, an increase in spherulite size with the increasing elastomer content (Fig.…”
Section: Spherulitic Morphology Of Ipp/sio 2 /Sebs-g-ma Compositesmentioning
confidence: 93%
“…The largest spherulites were observed in composites containing the S-D17 non-polar silica filler that exhibits the weakest nucleation ability because its surface is compatible with the iPP matrix. [15,32] Preferential iCS and SM morphologies with a significant iPPÀS-D17 interface area may reduce nucleation and additionally enhance the spherulite growth.…”
Section: Spherulitic Morphology Of Ipp/sio 2 /Sebs-g-ma Compositesmentioning
confidence: 99%
See 1 more Smart Citation
“…10,28 Relatively wide content range 0-20 vol % of added SEBS elastomer was used in order to research its efficiency as compatibilizer (5 vol %) as well as impact modifier and compatibilizer at higher SEBS content. The iPP/SiO 2 volume ratio was kept constant at 96/4 and 5, 10, 15, and 20 vol % of SEBS elastomer was added to 100 volume parts of composite (added 20 vol % of SEBS corresponds to 16.7 vol % of SEBS in total mass).…”
Section: Sample Preparationmentioning
confidence: 99%
“…Presented results confirm common findings in literature that the filler is not fully located only in one phase or only at interface. 10,27,28 Schematic presentation in Figure 4 reveals mainly interspherulitic acommodation of large micro-sized S-D17 particles beside some S-D17 particles engulfed by iPP spherulites. Polarization micrographs of binary iPP/silica composites indicated that silica particles with polar surfaces like A-R7200 more significantly decreased the spherulite size than silica particles with hydrophobic, non-polar surfaces like S-D17 due to stronger nucleation effect.…”
Section: Predicted Morphologies Of the Ipp/sio 2 /Sebs Compositesmentioning
confidence: 99%